PERANCANGAN STRUKTUR TAHAN GEMPA (SEISMIK) GEDUNG ESDM - Hariyanto, Hariyanto; Azizah, Nur Dita (Universitas PGRI Semarang, 2024)
Buildings are facilities that need to be fulfilled in an educational institution. The Ronggolawe Cepu Education Foundation has plans to build a workshop building located in Karangboyo Village, Cepu District. The construction of this building requires a good planning process so that the building being built can stand well. The structure is a building element that must be planned well because it functions to support the load of the building. In general, building structures are made of concrete and steel. This paper will discuss the structural planning of the Workshop building using concrete and steel materials.